Relationship of P Terminal Force V1 on Electrocardiogram with Left Atrial Function in Chronic Kidney Failure Patients on Hemodialysis - Kartika Apshanti; Putrika Prastuti Ratna Gharini; Hasanah Mumpuni (ACI (Acta Cardiologia Indonesiana), 2019)
Background: Chronic kidney failure is a worldwide public health problem.Cardiovascular disease is a common complication and the main cause of mortality in this population.Impaired left atrial function is an early marker of cardiovascular involvement and a prognostic factor that correlated with mortality in chronic kidney disease patients. We aimto investigate the relationship between P terminal force V1 (PTFV1), an ECG parameter, with left atrial function in chronic kidney failure patients on hemodialysis.Method: This cross sectional study was done in chronic kidney failure patients on hemodialysis in Dr. Sardjito General Hospital Jogjakarta. Electrocardiogram and echocardiography were done after hemodialysis procedure. P terminal force V1 was measured by multiplying amplitude and duration of negative deflection of terminal P wave in V1. Abnormal PTFV1 was defined as PTFV1 value ≥ 40 mm.msec. Left atrial function was measured using left atrial peak global longitudinal strain (LA PGLS).Results: This study was done in 71 patients with mean age 50 years old. Forty three subjects (61%) were men. Sixty four subjects (90%) had hypertension. Forty four subjects (62%) had abnormal PTFV1 on ECG. Mean LA PGLS was 24.89 ± 8.23%. No significant correlation was found between PTFV1 value with LA PGLS (r= -0.178; p=0.138). By multivariate analysis, left ventricular ejection fraction, left atrial diameter and hemodialysis duration (in months) were variables that independently correlated with LA PGLS. In subanalysis, amplitude of negative deflection of terminal P wave in V1 was significantly correlated with LA PGLS(r= -0.257, p= 0.031).Conclusions: This study reveals no correlation between P terminal force V1 and left atrial function in chronic kidney failure patients on routine hemodialysis. There is significant correlation between amplitude of negative deflection of terminal P wave in V1 with LA PGLS.